# CONTENT

Solving Systems of Linear
Equations by Substitution Method

Solving Systems of Linear
Equations by Elimination Method
Subtraction
SOLVING SYSTEMS OF
LINEAR EQUATION BY
SUBSTITUTION
METHOD
SUBSTITUTION
METHOD
It is a method of solving
systems of linear equations by
substituting the first equation
to the second equation or the
second equation to the first
equation.
Steps on solving SLE by
substitution:
 Use one of the equations to solve for
the “x” or the “y”.
 Next, plug that equation to the other
equation.
 After, solve the equation.
 Then, plug the answer to the other
equation.
point of intersection.
EXAMPLES:
1. x + y = 5
x – y = -1

Let’s use the second equation to
solve for “y”
 y = x + 1
Now, let’s plug this to the first
equation
 x + (x + 1) = 5
Then, let’s solve.
 x + (x + 1) = 5
 x + x + 1 = 5
 2x + 1 = 5
 2x = 5 – 1
 2x = 4
2 2
 x = 2
Now, let’s plug the “x” to the
second equation to find the
value of “y”
 x – y = -1
 2 – y = -1
 – y = -1 -2
 – y = -3
 y = 3
First Equation
x + y = 5
2 + 3= 5
5 = 5 TRUE
Second Equation
 x – y = -1
 2 – 3 = -1
 -1 = -1 TRUE {(2,3)}

2. 3x + y = 10
2x – y = 0

Let’s use the second equation to
solve for “y”
 y = 2x
Now, let’s plug this to the first
equation
 3x + (2x) = 10
Then, let’s solve.
 3x + (2x) = 10
 3x + 2x = 10
 5x = 10
 5x = 10
5 5
 x = 2
Now, let’s plug the “x” to the
second equation to find the
value of “y”
 2x – y = 0
 2(2) – y = 0
 4 – y = 0
 – y = 0 + -4
 – y = -4
 y = 4
First Equation
 3x + y = 10
 3(2) + 4= 10
 6 + 4 = 10
 10 = 10 TRUE
Second Equation
 2x – y = 0
 2(2) – 4 = 0
 4 – 4 = 0
 0 = 0 TRUE {(2,4)}

3. 5x + y = 10
3x – y = 6

Let’s use the second equation to
solve for “y”
 y = 3x – 6
Now, let’s plug this to the first
equation
 5x + (3x – 6) = 10
Then, let’s solve.
 5x + (3x – 6) = 10
 5x + 3x – 6 = 10
 8x = 10 + 6
 8x = 16
8 8
 x = 2
Now, let’s plug the “x” to the
second equation to find the
value of “y”
 3x – y = 6
 3(2) – y = 6
 6 – y = 6
 – y = 6 – 6
 – y = 0
 y = 0
First Equation
 5x + y = 10
 5(2) + 0 = 10
 10 + 0 = 10
 10 = 10 TRUE
Second Equation
 3x – y = 6
 3(2) – 0 = 6
 6 – 0 = 6
 6 = 6 TRUE {(2,0)}

4. 4x + y = 14
2x – y = 4

Let’s use the second equation to
solve for “y”
 y = 2x – 4
Now, let’s plug this to the first
equation
 4x + (2x – 4) = 14
Then, let’s solve.
 4x + (2x – 4) = 14
 4x + 2x – 4 = 14
 6x – 4 = 14
 6x = 14 + 4
 6x = 18
6 6
 x = 3
Now, let’s plug the “x” to the
second equation to find the
value of “y”
 2x – y = 4
 2(3) – y = 4
 6 – y = 4
 – y = 4 – 6
 – y = -2
 y = 2
First Equation
 4x + y = 14
 4(3) + 2= 14
 12 + 2 = 14
 14 = 14 TRUE
Second Equation
 2x – y = 4
 2(3) – 2 = 4
 6 – 2 = 4
 4 = 4 TRUE {(3,2)}

SOLVING SYSTEMS OF
LINEAR EQUATION BY
ELIMINATION METHOD
ELIMINATION
METHOD
It is a method of solving
systems of linear
equations by eliminating
subtraction.
Steps on solving SLE by substitution:
 Eliminate one of the variables, either “x” or “y”.
They should have the same constant, and
variable but different signs. If they have the
same constant, variable and sign, change the
signs of one of the equations.
 Next, add or subtract the remaining variable and
the constant.
Add if the variables have the same constant but
different signs, or there are no changes made.
Subtract if the sign of one of the variables have been
changed.
 Then, solve or simplify.
 After, plug the answer to one of the equations
and solve it.
intersection.
1. x + y = 5
x – y = -1

Let’s eliminate the variable “y” since
they have the same variable and
 (2x = 4) 1/2
 x = 2
Then, let’s plug in the
value of “x” to find the
value of “y” (use equation
one or two)
x + y = 5
2 + y = 5
y = 5 – 2
y = 3
First Equation
x + y = 5
2 + 3 = 5
5 = 5 TRUE
Second Equation
 x – y = -1
 2 – 3 = -1
 -1 = -1 TRUE {(2,3)}

2. 3x + y = 10
2x – y = 0

Let’s eliminate the variable “y”
since they have the same
variable and different signs
 (5x = 10) 1/5
 x = 2
Then, let’s plug in the value of
“x” to find the value of “y”
(use equation one or two)
3x + y = 10
3(2) + y = 10
6 + y = 10
y = 10 - 6
y = 4
First Equation
 3x + y = 10
 3(2) + 4= 10
 6 + 4 = 10
 10 = 10 TRUE
Second Equation
 2x – y = 0
 2(2) – 4 = 0
 4 – 4 = 0
 0 = 0 TRUE {(2,4)}

EXAMPLES (SUBTRACTION):
1. x + y = 5
2x + y = 7

Let’s change the sign of the variable
“y” so we can eliminate them
(since we change the sign we will
use subtraction)
 -x = -2
 x = 2
Then, let’s plug in the value of
“x” to find the value of “y”
(use equation one or two)
 x + y = 5
(2) + y = 5
2 + y = 5
y = 5 – 2
y = 3
First Equation
 x + y = 5
 2 + 3 = 5
 5 = 5 TRUE
Second Equation
 2x + y = 7
 2(2) + 3 = 7
 4 + 3 = 7
 7 = 7 TRUE {(2,3)}

2. 3x + y = 10
2x + y = 8

Let’s change the sign of the
variable “y” so we can eliminate
them (since we change the sign
we will use subtraction)
 x = 2
Then, let’s plug in the value of
“x” to find the value of “y”
(use equation one or two)
 3x + y = 10
3(2) + y = 10
6 + y = 10
y = 10 – 6
y = 4